Comparison of personality abilities, coping style with stress and self-efficacy in two groups of housewives and female teachers of the second secondary level of Kashan city - Goli , Zahra Sadat; Mirseify fard, Leila Sadat (Psychology of Woman Journal, 2022)
The present study was conducted to compare positive personality abilities, stress coping styles, and self-efficacy in two groups of housewives and female teachers of the second secondary level of Kashan city. In this research, a descriptive method with a causal-comparative approach has been used. The research population consisted of all female teachers of the second secondary level in Kashan city in 2018-2019 and housewives in Kashan city, who were selected as a sample in two groups of 180 people using the available sampling method. To collect data, Patterson and Seligman’s (2004) personality abilities questionnaire, Andler, and Packer’s (1990) stress coping style questionnaire, and Scherer et al.’s (1982) general self-efficacy questionnaire were used. In order to analyze the data, a t-test of two independent groups and an analysis of variance were used. In examining the hypothesis, the results showed that the average of the two groups of housewives (468.05) and female teachers (490.54) has a significant difference in the variable of personality abilities (p<0.05). Female teachers use the problem-oriented style with an average of 59.556, and housewives use the emotion-oriented style with an average of 56.56. Also, the average of the two groups of female teachers (60.41) and housewives (58.92) in the self-efficacy variable is not significantly different from each other (p>0.05). Therefore, it can be concluded that teachers are higher than housewives and female teachers in terms of personality abilities of wisdom, humanity, courage, justice, moderation, and excellence, female teachers use problem-oriented styles to deal with stressful situations, and housewives use emotional styles.